Probing synergetic effects between platinum nanoparticles deposited via atomic layer deposition and a molybdenum carbide nanotube support through surface characterization and device performance. Issue 23 (27th May 2016) - Saha, Shibely; Martin, Bridger; Leonard, Brian; Li, Dongmei
Abstract : A phase-pure molybdenum carbide modified by Pt ALD significantly reduced Pt loading while enhancing the activity and durability of the resultant catalysts. Abstract : Platinum (Pt) supported on transition metal carbide (TMC) surfaces (Pt/TMC) has been the focus of significant research interest, due to the similar electronic and geometric structures between TMC and Pt. This paper focuses on a new type of electrocatalyst fabrication using high purity β-molybdenum carbide (referred to as Mo2 C hereafter) nanotubes as a support and atomic layer deposition (ALD) as the Pt nanoparticle deposition technique (Pt/Mo2 C). In particular, rotary ALD equipment was used to grow Pt particles from the subnanometer level to 2 to 3 nanometers by simply adjusting the number of ALD cycles in order to probe the interaction between the deposited Pt nanoparticles and Mo2 C nanotube support. Lattice spacing analysis using high resolution transmission electron microscopy (HRTEM) images, combined with Pt binding energy shift in XPS results, clearly showed a strong interaction between Pt nanoparticles and the Mo2 C nanotube support in all the resultant Pt/Mo2 C samples. We postulate that this strong interaction is responsible for the significantly enhanced durability observed in constant potential electrolysis (CPE) testing. Of the three samples from different ALD cycles (15, 50 and 100), Mo2 C nanotubes modified by 50 (1.07 wt% Pt loading) and 100 cycles (4.4 wt% Pt) of Pt deposition showed higher activity per Pt mass than commercial 20% Pt supported on carbon black. Finally, we report the nanoscale Pt/Mo2 C catalyst performance in a device setting for different Pt loadings by applying it in a PEMFC anode.